ANALISIS PENGARUH PERSEPSI KEMUDAHAN, PERSEPSI KEMANFAATAN, PERSEPSI TINGKAT KEAMANAN, DAN FITUR LAYANAN TERHADAP PENGGUNAAN MOBILE BANKING PADA MAHASISWA DI DKI JAKARTA - Kristianti, Maria Loki; Pambudi, Rilo (Program Studi Akuntansi Fakultas Ekonomi dan Bisnis Universitas Katolik Indonesia Atma Jaya, 2017)
This research aimed to analyze of perceived ease of use, perceived usefulness, perceived level of security, and service features effect using mobile banking by students in Jakarta. This research took samples of 200 students from universities in Jakarta that using mobile banking or want to use mobile banking. The results showed that perceived ease of use, perceived usefulness, perceived level of security, and service features affect using mobile banking by students in Jakarta.